Analisis Pelaksanaan Layanan Bimbingan dan Konseling oleh Guru BK di Sekolah yang Tidak Diberikan Alokasi Jam Masuk Kelas - Qomariyah, Ida Nur; Maradika, Agitha Wigati Yulistyo; Salsabila, Faza; Amelia, Ummahatul Nur; Lianawati, Ayong (Sociocouns: Journal of Islamic Guidance and Counseling, 2025)
This study aims to examine the implementation of Guidance and Counseling services in schools that do not provide regular class time allocation for Guidance and Counseling teachers. Using a qualitative case study approach, data were obtained through interviews and observations during introduction to the school field at Senior High School AL-ISLAM Krian. The results of the study indicate that limited time allocation is the main challenge in providing comprehensive Guidance and Counseling services. Guidance and Counseling teachers only get the opportunity to enter the classroom twice in one semester, so the service is more reactive and does not reach all students evenly. To overcome these obstacles, Guidance and Counseling teachers implement adaptive strategies such as utilizing social media, collaborating with homeroom teachers and subject teachers, and integrating into extracurricular activities. These findings indicate that the effectiveness of Guidance and Counseling services is highly dependent on creativity, time management, and school policy support. The research recommendations emphasize the importance of reviewing the policy of class time allocation to support the success of comprehensive and sustainable Guidance and Counseling services in the educational environment.